A business attribute correlation multi-path routing algorithm based on SDN architecture - Xiang YU; Mingmin YI; Lu YANG (Dianxin kexue)
Currently,most of the routing algorithms support only one QoS parameter,and do not consider the fairness of system scheduling service.Obviously,multi-parameters constrains problem is NP hard problem,it is impossible to solve this kind of problem by traditional routing algorithms.The routing thought from ant colony algorithm（ACO）was introduced.On the basis of the ACO,and combined with the business attributes of traffic flow,a new algorithm was put forward which introduced the delay and packet loss into the ACO,as a dependence of routing.In new algorithm,which according to the real-time status of network,the suitable routing was chosen for different types traffic and forward by multi-path base on the classification of traffic flows.The experiment shows that this algorithm can decrease the delay and packet loss effectively.